If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -18 = 5x + 12 Reorder the terms: -18 + 3x = 5x + 12 Reorder the terms: -18 + 3x = 12 + 5x Solving -18 + 3x = 12 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -18 + 3x + -5x = 12 + 5x + -5x Combine like terms: 3x + -5x = -2x -18 + -2x = 12 + 5x + -5x Combine like terms: 5x + -5x = 0 -18 + -2x = 12 + 0 -18 + -2x = 12 Add '18' to each side of the equation. -18 + 18 + -2x = 12 + 18 Combine like terms: -18 + 18 = 0 0 + -2x = 12 + 18 -2x = 12 + 18 Combine like terms: 12 + 18 = 30 -2x = 30 Divide each side by '-2'. x = -15 Simplifying x = -15
| 65=5x-15 | | 5w+9=-(4w+11) | | 500+560+640n=10000 | | -6(x-2)-8m=-2 | | 3-8+200= | | 2x=45+x | | 3y+5=t | | 11-2x=31-7 | | 3p^2=-10p-8 | | 4x+2-7x+5=6x-9x+6 | | 3(x+4)+x=16 | | r-(-2)=2 | | 4*3+x=60 | | 4(u+1)+u=3(u-2)+2 | | 8-x=4 | | 12-y= | | 7+c=-3 | | 7t+6.1=9.6 | | 5x-2.2=10.3 | | x+4=-(6x+6) | | 25+3x=7x | | a-44=2 | | 4a+7=2a+3 | | 12a+6.2=42.2 | | 2x^2=3x+10 | | r+3=2 | | x+8=-2(2x+2) | | 7(x-2)=4(x-3) | | 22.3=4y+1.5 | | 9d-3.1=14.9 | | 5r+6.3=8.8 | | 9-7m=1-8m |